An evaluation of post-production facial composite enhancement techniques. Issue 4 (9th November 2015) - Davis, Josh P; Simmons, Stacie; Sulley, Lucy; Solomon, Chris; Gibson, Stuart
Abstract : Purpose: – The purpose of this paper is to describe four experiments evaluating post-production enhancement techniques with facial composites mainly created using the EFIT-V holistic system. Design/methodology/approach: – Experiments 1-4 were conducted in two stages. In Stage 1, constructors created between one and four individual composites of unfamiliar targets. These were merged to create morphs. Additionally in Experiment 3, composites were vertically stretched. In Stage 2, participants familiar with the targets named or provided target-similarity ratings to the images. Findings: – In Experiments 1-3, correct naming rates were significantly higher to between-witness 4-morphs, within-witness 4-morphs and vertically stretched composites than to individual composites. In Experiment 4, there was a positive relationship between composite-target similarity ratings and between-witness morph-size (2-, 4-, 8-, 16-morphs). Practical implications: – The likelihood of a facial composite being recognised can be improved by morphing and vertical stretch. Originality/value: – This paper improves knowledge of the theoretical underpinnings of these facial composite post-production enhancement techniques. This should encourage acceptance by the criminal justice system, and lead to better detection outcomes.